2008
DOI: 10.1089/gte.2007.0089
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Transporter Gene Polymorphisms and Sertraline Response in Major Depression Patients

Abstract: Major depression (MD) has a complex multifactorial etiology with genetic and environmental factors contributing to the disorder. As with all antidepressant treatments, there is variability in drug response due to heredity, generally focusing on genetic polymorphism of the drug-metabolizing transporter genes. The serotonin transporter (5-HTT) gene is a particularly important candidate for genetic involvement in MD disorders owing to its key role in the regulation of serotonergic transmission and is therefore co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…However, a number of studies conducted on Caucasian-dominant groups did not show similar results, with the s allele being associated with better treatment response/remission [46,47], or with the insertion/deletion genotype having no effect on treatment [48,49]. Studies conducted on Asian patients have shown even more opposing results on which variant is the favorable one for antidepressant treatment [18,19,35].…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies conducted on Caucasian-dominant groups did not show similar results, with the s allele being associated with better treatment response/remission [46,47], or with the insertion/deletion genotype having no effect on treatment [48,49]. Studies conducted on Asian patients have shown even more opposing results on which variant is the favorable one for antidepressant treatment [18,19,35].…”
Section: Discussionmentioning
confidence: 99%
“…163 These findings are generally well replicated in studies involving white popu lations, 120,[164][165][166][167][168][169][170][171][172][173][174][175] although opposite or inconsistent findings have also been reported. [176][177][178][179][180] On the other hand, studies involving Asian populations usually report conflicting results: some studies reported that the short 5-HTTLPR allele was associated with better outcomes, [181][182][183][184] some found no effect of 5-HTTLPR genotype on treatment efficacy 121,185,186 and some reported that the long 5-HTTLPR allele was associated with better outcomes. 83,[187][188][189][190][191] Interestingly, Lotrich and colleagues 192 recently reported that paroxetine blood concentration was positively associated with HAM-D response in a sample of elderly patients, but this association was found to be significant only in carriers of the short allele.…”
Section: Comtmentioning
confidence: 99%
“…Another polymorphism influencing SERT expression, described as 17bp VNTR polymorphism, was identified within intron 2 (STin2) [80]. Several studies reported an influence of STin2 on response to ADs, but other investigations were not able to repeat these findings [81][82][83][84][85]. Moreover, it was proposed that STin2 10/12 genotype may be associated with poorer antidepressant effect, especially in Asian populations [86].…”
Section: Serotonin Transporter (Slc6a4)mentioning
confidence: 99%